How Peace Operations Work: Power, Legitimacy, and Effectiveness by Jeni Whalan - Umair Khalid Ameen (NUST Journal of International Peace and Stability)
This book review examines an insightful study on peace operations, focusing on their power, legitimacy, and effectiveness in influencing local actors. The author explores the moral and ethical debates surrounding international interventions, referencing key scholarly works on sovereignty, state-building, and conflict resolution. By analyzing theoretical perspectives, including realist and neoliberal approaches, the book highlights the complexities of authority and legitimacy in peacekeeping. It provides a detailed examination of case studies such as the United Nations Transitional Authority in Cambodia (UNTAC) and the Regional Assistance Mission to Solomon Islands (RAMSI), applying a newly developed power–legitimacy framework. The book also emphasizes the psychological and political dimensions of peace operations, outlining essential factors for their success. Through a critical analysis of existing literature and case studies, the author presents policy recommendations for improving peacekeeping effectiveness. This work is a valuable contribution to peace and conflict studies, offering fresh perspectives on the challenges and prospects of international peace operations.